Mass Transfer of Natural Dye Extraction and the Degradation Rate - Mindaryani, Aswati; Rahayuningsih, Edia; Zahra, Aulia; Wardani, Erina Endah Kusuma (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
This research studied the effect of temperature on the mass transfer rate and degradation rate of natural dye extraction. As the representative, two natural dyes extracted from Senduduk and Susupan Gunung plants were employed. Senduduk and Susupan Gunung are weed plants that are often found in peatlands. Susupan Gunung is easily found in South Kalimantan, and local people use it as a natural dye for handicraft products. Senduduk is often found in the South Sumatra area also used as a natural dye for traditional fabrics. Senduduk and Susupan Gunung were extracted in a three-neck flask using water as a solvent at temperatures of 50°, 70°, and 90°C. Samples of the extract solution were taken at certain times until the tannin concentration was constant. The tannin concentration in the solution was analyzed using volumetric methods. Experimental data consists of tannin concentrations in solution at various times. The mass transfer coefficient, equilibrium constant, and tannin degradation rate constant were determined by minimizing the sum square of errors between experimental data and the model. Senduduk contains more tannin (0.0094 g/cm3 solution) than Susupan Gunung (0.0079 g/cm3 solution), and Senduduk has a higher mass transfer coefficient than Susupan Gunung. The higher the temperature, the greater the rate of tannin degradation. During the extraction process, extract of Senduduk and Susupan Gunung leaves are stable at 50°C, which tends to degrade faster at higher temperatures.